(1)
1
a 1 +
1
a 2 +
1
a 3 +…+
1
a 2011 =2011 2
1
a 1 +
1
a 2 +
1
a 3 +…+
1
a 2010 =2010 2
两式相减得
1
a 2011 =2011 2-2010 2=4021⇒a 2011=
1
4021
(2)
1
a 1 +
1
a 2 +
1
a 3 +…+
1
a n =n 2
1
a 1 +
1
a 2 +
1
a 3 +…+
1
a n+1 =(n+1) 2
两式相减得
1
a n =n 2-(n-1) 2=2n-1⇒ a n =
1
2n-1 (n≥2)
当n=1时,a 1=1也满足上式∴ a n =
1
2n-1 (n≥1)
b n=a na n+1=
1
(2n-1)(2n+1) =
1
2 (
1
2n-1 -
1
2n+1 )
S n=
1
2 [(1-
1
3 )+(
1
3 -
1
5 )+…+(
1
2n-1 -
1
2n+1 )]=
1
2 (1-
1
2n+1 )
存在正整数b,使得S n>λ-
1
2 ,即S n的最大值大于λ-
1
2
而S n=
1
2 (1-
1
2n+1 )<
1
2
∴
1
2 >λ-
1
2 ,即λ<1